2018
DOI: 10.1021/acs.biochem.7b01156
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Cysteine 81 Residue of Macrophage Migration Inhibitory Factor as a Molecular Redox Switch

Abstract: Macrophage migration inhibitory factor (MIF) is a pro-inflammatory and tumor-promoting cytokine that occurs in two redox-dependent immunologically distinct conformational isoforms. The disease-related structural isoform of MIF (oxMIF) can be specifically and predominantly detected in the circulation of patients with inflammatory diseases and in tumor tissue, whereas the ubiquitously expressed isoform of MIF (redMIF) is abundantly expressed in healthy and diseased subjects. In this article, we report that cyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Based on biochemical and immunochemical experiments, it was suggested that this antibody recognizes an oxidized form of MIF with the oxidoreductase motif of MIF trapped in an oxidized state, and that Cys-81 serves as a molecular redox switch between the latent reduced form of MIF and its oxidized state. 93,98,99 While the antibody was reported to detect an oxidized MIF species termed 'oxMIF' in tumour tissue from patients with colorectal, pancreatic, ovarian and lung cancer, 100 the claim that oxMIF is the pathophysiologically relevant MIF species appears speculative and convincing evidence that imalumab targets pathogenic oxMIF species is missing. 67,95 MIF-2/D-DT shares with MIF a pronounced pro-inflammatory activity profile and has been reported to promote endotoxaemia, adipose tissue inflammation and tumorigenesis similar to MIF.…”
Section: Antibody-based Anti-mif Strategiesmentioning
confidence: 99%
“…Based on biochemical and immunochemical experiments, it was suggested that this antibody recognizes an oxidized form of MIF with the oxidoreductase motif of MIF trapped in an oxidized state, and that Cys-81 serves as a molecular redox switch between the latent reduced form of MIF and its oxidized state. 93,98,99 While the antibody was reported to detect an oxidized MIF species termed 'oxMIF' in tumour tissue from patients with colorectal, pancreatic, ovarian and lung cancer, 100 the claim that oxMIF is the pathophysiologically relevant MIF species appears speculative and convincing evidence that imalumab targets pathogenic oxMIF species is missing. 67,95 MIF-2/D-DT shares with MIF a pronounced pro-inflammatory activity profile and has been reported to promote endotoxaemia, adipose tissue inflammation and tumorigenesis similar to MIF.…”
Section: Antibody-based Anti-mif Strategiesmentioning
confidence: 99%
“…Secondly, Cys-80 is believed to act as a “switch cysteine” for the conversion of redMIF to the disease-related isoform oxMIF. 30 Covalent modification of Cys-80 with a series of pro-oxidative reagents showed that while some precipitated the conversion to oxMIF, at least one covalent adduct remained in the reduced form. This finding might indicate that a covalent inhibitor may be capable of trapping the comparatively benign redMIF oxidation state.…”
Section: Modes Of Inhibition: a Closer Lookmentioning
confidence: 99%
“…MIF, but not D-DT, has a CXXC motif that can be oxidized to an intramolecular disulfide-bond. Oxidised MIF has also been proposed as a biomarker for different diseases [28]. Other studies indicate that oxidized MIF is the disease-related conformational isoform that could be employed for diagnosis and therapy [29][30].…”
Section: Introductionmentioning
confidence: 99%